Studi Analisis Konsep Insan Kamil Menurut Abdul Karim Al-Jili dan Pemikiran Adi Hidayat - Dluha, Arba; Damanik, Nurliana (Lembaga Yasin AlSys, 2024)
Studying the debate surrounding Insan Kamil is fascinating. Two individuals that talk about the perfect human being are Adi Hidayat and Abdul Karim al-Jili. These two individuals provide their own explanations of the Insan Kamil idea. The opinions of Adi Hidayat and Abdul Karim al-Jili regarding Insan Kamil will be discussed in this article. This study falls under the category of library research, which entails the processing and analysis of data gathered from textual sources such as books, papers, journals, theses, and others. Qualitative, deductive, and comparative methodologies were used in the analysis. According to the findings, there are a number of comprehension, mental processes, and level disparities between Abdul Karim al-Jili and Adi Hidayat. Human Kamil is intelligent, knowledgeable, and perceptive. Human Kamil is intelligent and knowledgeable, and he is aware of his responsibilities as a caliph. Al-Jili describes the Prophet Muhammad SAW as the image of God, Insan Kamil as the ideal Tajalli of God, and God as the primary figure. Adi Hidayat dubbed Insan Kamil Ma'rifatul Insan, which translates to